Consumer Perception Towards Food Safety - Chung, Joo Chen (2007)
The main objective of this research was to analyze consumers' perception towards food safety. The theoretical framework has been developed in order to investigate the relationship between consumers' perception towards food safety as assessed by the five variables namely, organic foods, genetically modified (GM) foods, labelling, risk reduction and premium branded foods.